Production of Xylanase Enzyme from AspergillusTerreus SUK-1 - Ali, Abdalla A. M.; Hawege, Emsalem Faraj; Almatar, Manaf; Heyam, I. M. Al-Astal; Aladdin, Azzam (Sphinx Knowledge House, 2014)
Xylanase productionfrom AspergillusterreusSUK-1 was carried out in submerged culture fermentation (SCF). The fermentation process was performed by using 0.30% ofxylan and 0.75%  -cellulose as substrates of carbon source at 30°C, 150 rpm in the shaker for 7 days. Two processes, which were used for xylanaseproduction, were shake flask culture and fermenter. In the shake flask culture, the maximum xylanase activity was 52.18U/mL U/mL with xylan as a substrate, while 63.29U/mL was for a-cellulose as substrate; after 5 days. In 5 L fermenter with 3 L working volume, the xylanase activity reached the maximum value which was 78.65U/mLafter five days. Two conditions were studied to get the optimum conditions for xylanase activities which were pH and temperature by using xylan as substrate. The highest activity was at pH 6.5 and constant temperature 37°C. While the optimum temperature was 50°C with constant pH 5.